Comparison of annual percentage change in breast cancer incidence rate between Taiwan and the United States—A smoothed Lexis diagram approach. (31st May 2017) - Chien, Li‐Hsin; Tseng, Tzu‐Jui; Chen, Chung‐Hsing; Jiang, Hsin‐Fang; Tsai, Fang‐Yu; Liu, Tsang‐Wu; Hsiung, Chao A.; Chang, I‐Shou
Abstract: Recent studies compared the age effects and birth cohort effects on female invasive breast cancer (FIBC) incidence in Asian populations with those in the US white population. They were based on age–period–cohort model extrapolation and estimated annual percentage change (EAPC) in the age‐standardized incidence rates (ASR). It is of interest to examine these results based on cohort‐specific annual percentage change in rate (APCR) by age and without age–period–cohort model extrapolation. FIBC data (1991–2010) were obtained from the Taiwan Cancer Registry and the U.S. SEER 9 registries. APCR based on smoothed Lexis diagrams were constructed to study the age, period, and cohort effects on FIBC incidence. The patterns of age‐specific rates by birth cohort are similar between Taiwan and the US. Given any age‐at‐diagnosis group, cohort‐specific rates increased overtime in Taiwan but not in the US; cohort‐specific APCR by age decreased with birth year in both Taiwan and the US but was always positive and large in Taiwan. Given a diagnosis year, APCR decreased as birth year increased in Taiwan but not in the US. In Taiwan, the proportion of APCR attributable to cohort effect was substantial and that due to case ascertainment was becoming smaller. Although our study shows that incidence rates of FIBC have increased rapidly in Taiwan, thereby confirming previous results, the rate of increase over time is slowing. Continued monitoring of APCR and further investigation of the cause of the APCR decrease in Taiwan are warranted. Abstract : Although the incidence rates of FIBC have increased rapidly in Taiwan, thereby confirming previous results, the increase is slowing down.